RESPONSE OF BROILERS TO DIMETHYLGLYCINE ADDITION TO NORMAL AND LOW-ENERGY DIET ON PHYSIOLOGICAL PERFORMANCE AND ANTIOXIDANT STATUS - A. A. Hazaa; H. H. Nafe (مجلة الأنبار للعلوم الزراعية)
The experiment was conducted at the poultry field belong to Department of Animal Production/ College of Agriculture/ University of Anbar, from 09/03/2022 to 10/14/2022 (42 days), 180 Ross 308 one-day-old were used with an average weight of 37.8 grams distributed over 6 treatments with 3 replicates per treatment (10 chicks per replicate) DMG (dimethylglycine) was used. glycine) as a diet additive. This study aimed to examine the response of broilers to addition of dimethylglycine (DMG) to the normal and low-energy diet in terms of physiological performance from one day to marketing age (42) days. Birds were fed on two dietary systems: the first bishop feature that included transactions (T1, T2, T3), the first transaction T1 was control without adding (normal diet), the second transaction T2 and the third T3 (adding DMG at 300 and 600 mg/ kg ordinary diet sequential First treatment without adding (T1, T2, T3). 300 and 600 mg/kg low-energy rations, respectively). an improvement (P < 0.05) in favor of the low-energy diet with the addition of DMG at the level of 600 mg / kg feed for ALP enzyme, and a significant improvement (P < 0.05) was observed in the number of lymphocytes in favor of the normal and low-energy diet when adding DMG at the level of 600 mg / kg feed. Dimethylglycine has a protective role against damage caused by oxidative stress and works to stimulate immunity